Investigate the incidence and prevalence of Nonarteritic Anterior Ischemic Optic Neuropathy (NAION) in patients taking semaglutide (Ozympic). - Amiruddin, Muhammad Usman; Akhtar, Naheed; Mustafa, Koonj; Gondal, Ali Hussain; Sadikan, Muhammad Zulfiqah; Jaiperkash, Jaiperkash (Journal of Neonatal Surgery, 2025)
NAION is a severe form of vision loss and the onset of anamorphic, painless vision loss, and in most cases, it is linked to risk factors that are systemic including diabetes and hypertension. The objective of this study was to evaluate the risk of NAION as a result of semaglutide use in a systematic review of literature that supports the claim by examining the incidence, the risk factors and potential mechanisms of the relationship between the two. A literature review of the publications on the topic published in January 2024-June 2025 was carried out. The included studies were those that evaluate the risk of NAION in patients under semaglutide treatment, which comprise studies in the cohort category, clinical trials, and case reports. Hazard ratios (HR) data, 95% confidence interval (CI) data and incidence rate data were extracted and analyzed. Five studies were analyzed and reported different findings on the correlation between semaglutide and NAION. There was a report of substantial increase in the hazard ratio (HR of 2.58 up to 4.28) by certain studies whereas there was no significant risk increase in others. Most studies had confidence intervals that were wide indicating variation in results. Small Bruchs membrane opening (BMO) and crowded optic discs were risk factors that were found to predispose NAION in semaglutide users. Although risk of NAION in people taking semaglutide seems to be low in the general population, there are some subgroups which may face this risk especially those that have predisposing ocular risk factors. The general therapeutic advantages of semaglutide in the treatment of type 2 diabetes and obesity offset the risks that the drug poses to the eyes of the majority of patients..